Minimally Invasive Versus Open Transforaminal Lumbar Interbody Fusion Surgery: An Analysis of Opioids, Nonopioid Analgesics, and Perioperative Characteristics. Issue 6 (September 2019) - Hockley, Aaron; Ge, David; Vasquez-Montes, Dennis; Moawad, Mohamed A.; Passias, Peter Gust; Errico, Thomas J.; Buckland, Aaron J.; Protopsaltis, Themistocles S.; Fischer, Charla R.
Study Design: Retrospective study of consecutive patients at a single institution.Objective: Examine the effect of minimally invasive surgery (MIS) versus open transforaminal lumbar interbody fusion (TLIF) surgery on long-term postoperative narcotic consumption. Objective: Examine the effect of minimally invasive versus open TLIF on short-term postoperative narcotic consumption. Methods: Differences between MIS and open TLIF, including inpatient opioid and nonopioid analgesic use, discharge opioid use, and postdischarge duration of narcotic usage were compared using appropriate statistical methods. Results: A total of 172 patients (109 open; 63 MIS) underwent primary TLIF. There was no difference in baseline characteristics. The MIS TLIF cohort had a significantly shorter operative time (223 vs 251 min, P = .006) and length of stay (2.7 vs 3.7 days, P < .001) as well as less estimated blood loss (184 vs 648 mL, P < .001). MIS TLIF had significantly less total inpatient opioid usage (167 vs 255 morphine milligram equivalent [MME], P = .006) and inpatient oxycodone usage (71 vs 105 mg, P = .049). Open TLIF cases required more ongoing opiate usage at 3-month follow-up (36% open vs 21% MIS, P = .041). A subanalysis found that patients who underwent an open TLIF with a history of preoperative opioid use are significantly more likely to remain on opioids at 6-week follow-up (87% vs 65%, P = .027), 3-month follow-up (63% vs 31%, P = .008), and 6-month follow-up (50% vs 21%, P = .018) compared with MIS TLIF. Conclusion: Patients undergoing MIS TLIF required less inpatient opioids and had a decreased incidence of opioid dependence at 3-month follow-up. Patients with preoperative opioid use undergoing MIS TLIF are less likely to require long-term opioids.